Demonstration of Shot-noise-limited Swept Source OCT Without Balanced Detection - Vala Fathipour (Nature Portfolio, 2017)
Abstract Optical coherence tomography (OCT) has been utilized in a rapidly growing number of clinical and scientific applications. In particular, swept source OCT (SS-OCT) has attracted many attentions due to its excellent performance. So far however, the limitations of existing photon detectors have prevented achieving shot-noise-limited sensitivity without using balanced-detection scheme in SS-OCT, even when superconducting single-photon detectors were used. Unfortunately, balanced-detection increases OCT system size and cost, as it requires many additional components to boost the laser power and maintain near ideal balanced performance across the whole optical bandwidth. Here we show for the first time that a photon detector is capable of achieving shot noise limited performance without using the balanced-detection technique in SS-OCT. We built a system using a so-called electron-injection photodetector, with a cutoff-wavelength of 1700 nm. Our system achieves a shot-noise-limited sensitivity of about −105 dB at a reference laser power of ~350 nW, which is more than 30 times lower laser power compared with the best-reported results. The high sensitivity of the electron-injection detector allows utilization of micron-scale tunable laser sources (e.g. VCSEL) and eliminates the need for fiber amplifiers and highly precise couplers, which are an essential part of the conventional SS-OCT systems.